Effect of extruded whole soybean dietary concentrate on conjugated linoleic acid concentration in milk in Jersey cows under pasture conditions - Avilez Ruiz, J. P.; Escobar, P.; Díaz, C.; von Fabeck, G.; Matamoros, R.; García, F.; Alonzo, M.; Delgado Pertiñez, M. (Spanish Journal of Agricultural Research, 2012)
Contradictory results has been found on the effects of soybean supplementation and conjugated linoleic acid (CLA) content in milk on feeding systems based on fresh forage The objective of the study was to evaluate the effect of a dietary supplement with different quantities of extruded whole soybean on the production and composition of milk, and CLA concentration or their isomers in Jersey cows under pasture conditions. Twenty-one Jersey cows were randomly assigned into 3 groups of 7 animals each. The cows were supplemented with a dietary concentrate (5 kg d-1), and each group received one of the three next treatments: control without soybean (0-SB), with extruded whole soybean at 0.5 kg d-1 (0.5-SB) or at 1 kg d-1 (1-SB). The basic diet was a pasture composed of Lolium perenne (70%), Trifolium repens (25%) and other species. The duration of the study was 75 d. Milk production (p = 0.706) and protein production (p = 0.926) were not affected by treatments. Fat (p = 0.015) and protein (p = 0.045) content as well as fat production (p = 0.010) were lower in the 1-SB group. There was no effect of the inclusion of extruded soybean on total CLA content (p = 0.290) or the content of cis-9, trans-11 (p = 0.582), trans-10, cis-12 (p = 0.136) and cis-10, cis-12 (p = 0.288) isomers. However, concentrations of all isomers were affected by the nutritional quality of the pasture, with low values observed at greater maturity stages of pasture.